2020
DOI: 10.1590/s1983-41952020000600002
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the structural system with composite beam and composite slab using Genetic Algorithm

Abstract: The objective of this research is to create a software to optimize choice variables adopted by an engineer in a structural system with steel-concrete composite beams and steel decks, such as: beam shape, composite slab sheeting, number and spacing of beams, slab thickness and interaction ratio between beam and slab. To accomplish this, a program that uses the Genetic Algorithm optimization tool provided by Matlab R2015a was developed. To meet safety requirements, restrictions on the Ultimate Limit State were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…This example presents an application of the methodology proposed herein to the Nexem building -Nucleous of Excelence in Metallic Structures (direct translation from Portuguese), shown in Figure 7. This example is also analyzed by Breda et al [28]. The structure is located at Goiabeiras campus of the Federal University of Espírito Santo (UFES) and features a composite girder and slab system with a constructed area of 264.98 m 2 .…”
Section: Example 2 -Case Study Of the Nexem Buildingmentioning
confidence: 98%
See 2 more Smart Citations
“…This example presents an application of the methodology proposed herein to the Nexem building -Nucleous of Excelence in Metallic Structures (direct translation from Portuguese), shown in Figure 7. This example is also analyzed by Breda et al [28]. The structure is located at Goiabeiras campus of the Federal University of Espírito Santo (UFES) and features a composite girder and slab system with a constructed area of 264.98 m 2 .…”
Section: Example 2 -Case Study Of the Nexem Buildingmentioning
confidence: 98%
“…The design of the composite structural elements followed the standardized procedures provided by ABNT NBR 8800:2008 [26], based on limit-state design. It's Annex O of the standard prescribes the guidelines for the design of steel-concrete composite beams, while the design procedure for steel-concrete composite slabs is shown in Annex Q. Breda et al [28] presented a formulation for the optimization problem analyzed here. However, the analysis performed by the authors was limited to cost optimization of the slabs and primary beams.…”
Section: The Problem Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained were like those already used in practical cases. Breda et al [10] presented a numerical optimization process, using the commercial software MATLAB as the main computational tool, for the optimization of steel-concrete composite beams and steel deck systems. The study demonstrated that increasing the number of beams, while reducing its individual weight, results in smaller slab spans and, consequently, in a reduction of the overall weight and costs.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of a multi-objective problem [26][27][28][29] considering cost and environmental impacts, a more iterative analysis is required to derive an optimal design proposal that minimizes the objective function while satisfying structural safety. A genetic algorithm (GA) is a good tool to solve the multi-objective problem [30], and the analysis time can be greatly reduced through the improvement of the algorithm [31]. However, when the composition of the steel-concrete beam is changed, it is necessary to calibrate the structural or design parameters constituting the GA.…”
Section: Introductionmentioning
confidence: 99%